Detection of Tn916 Conferring Tetracycline Resistance in Clinical Isolates of Streptococcus pyogenes (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: During the past twenty years, tetracycline resistance average has increased in Streptococcuspyogenes in many countries. Pneumococcal resistance to erythromycin and tetracycline is associated withthe insertion of the erm(B) into the transposons of the Tn916 family. To get datum that may be beneficial inresolving the diffusion of antimicrobial resistance, therefore, we can be specified antibiotic resistant genesand their corporation with mobile genetic elements. This study was proceed to explore the genetic regulationof Tn916-carrying tet(M) in clinical isolates of S.pyogenes . Methods: A twenty two of S.pyogenes isolateswere assemble from patients suffering from upper respiratory infection, and the susceptibility of theseisolates to tetracycline antibiotics was examined. Molecular detection of Tn916 was carried out by employcertain primers to amplify tet(M) gene in each isolates.Results: The results appeared that the resistance of the tetracycline group was 68.1%, 54.5%, 36.3% and31.8% for minocycline, tetracycline, oxytetracycline and doxycycline, respectively. Genetic analysis showedthat Tn916 was detected in eight of the S.pyogenes clinical isolates resistant to tetracycline. Conclusions:Our findings suggest that clinical isolates of S. pyogenes harboring a copy(s) of Tn916 conferring tetracyclineresistance. One possible explanation for resistance to tetracycline in these isolates is due to tet gene, whichwas most likely located on Tn916.